Integrated talent management strategy in the Polish Air Forces in the context of the well-being of cadets and soldiers - Małgorzata Zielińska (Nowoczesne Systemy Zarządzania)
Research objectives and hypothesis/research questions Research problem was the analysis of changing process of implementing elements of talent management strategy among cadets and soldiers of The Polish Air Forces. 1. What kinds of changes are in carrying on talent management processes in the Polish Air Forces? 2. What kinds of elements of talent management strategy are integrated in 2015-2023? 3. Is the multidimensional talent management strategy implementing in the Polish Air Forces? 4. Is talent management strategy the cause of reaching well-being by cadets and soldiers?